Thiamethoxam affects the developmental stages of banded gourami (Trichogaster fasciata) - Mohibul Hasan; Kizar Ahmed Sumon; M.A. Mamun Siddiquee; Ramji Kumar Bhandari; Mohammad Dalower Hossain Prodhan; Harunur Rashid (Toxicology Reports, 2022)
Thiamethoxam (THM), a type III systemic neonicotinoid insecticide, is widely used in agriculture in many countries, including Bangladesh. THM can enter the aquatic systems through the runoff, spray-drift and groundwater leaching and can affect the aquatic organisms, including fish. Current environmental levels of THM in Bangladesh waters are variable. However, the presence of this chemical in the aquatic environment and its possible effects on the fish inhabiting those water bodies is concerning. To understand the effects of environmental THM on the development of embryo and larvae, the present study used banded gourami (Trichogaster fasciata), a freshwater fish species distributed in different Asian countries, including Bangladesh. In laboratory setting, fertilized eggs (n = 100) and one-day-old banded gourami larvae (n = 100) were exposed to six concentrations of THM (0, 0.02, 0.2, 2, 20, 200 mg/L) in three replicates, in which three concentrations were within the environmentally relevant levels. Hatching rate, incubation period, mortality, and malformations of embryo and larvae were observed. The hatching success and survival of embryo and larvae significantly decreased with increasing THM concentrations. The 24-h LC50 of THM for the embryo was 4.24 mg/L. The 24-h, 48-h, 72-h, and 96-h LC50 values of THM for one-day-old larvae were 12.20, 3.80, 0.78, and 0.27 mg/L, respectively. Overall developmental malformations included lordosis, notochord abnormality, yolk-sac edema, dark brown yolk sac, hemorrhage, and irregular caudal fin. These abnormalities in embryos were common across all the concentrations of THM applied. The results of the present study suggest that environmentally relevant concentrations of THM can induce developmental defects in the embryo and larvae of banded gourami.